Kemampuan Menulis Teks Laporan Hasil Observasi Melalui Metode Kolaborasi Pada Siswa Kelas VIIG SMP Negeri 3 Kupang Tahun Pelajaran 2025/2026 - Libna Yunita Bayfeto; Sanhedri Boimau; Ona Diana Bani; Arnot Kolnel (Kampus Akademik Publiser, 2026)
The problem in this study is how the ability of seventh-grade G students of SMP Negeri 3 Kupang in writing observation report texts. The purpose of this study is to describe the ability of seventh-grade G students of SMP Negeri 3 Kupang in writing observation report texts. The benefits are: for students, as an effort to improve their ability to write observation report texts; for readers, it can serve as reflective material for researching writing skills in observation report texts; for researchers, this study is expected to provide new insights and experiences regarding the learning activities of writing report text skills; and for subject teachers, as input for providing further guidance to students who experience difficulties in writing report text activities. The approach used is a normative approach. A normative approach is a research method that focuses on examining and evaluating a phenomenon or object under study based on established standards, values, or norms. The method used is descriptive qualitative. Descriptive qualitative is a research working mechanism that relies on descriptive explanations of words or sentences arranged carefully and systematically, starting from data collection to interpreting and reporting the research results. The results of the study on the ability to write observation report texts through the collaborative method among seventh-grade G students of SMP Negeri 3 Kupang in the 2025/2026 academic year show that the percentage of students who obtained a very good score was 13 students (52%), students in the good category amounted to 7 students (28%), and students in the fairly good category amounted to 5 students (20%). Thus, the ability to write observation report texts through the collaborative method among seventh-grade G students of SMP Negeri 3 Kupang in the 2025/2026 academic year, classically, falls into the good category with a class average score of 84.28.